2002
DOI: 10.1111/j.1348-0421.2002.tb02719.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Escape Mutants of Rabies Virus Which Are Resistant to Neutralization by a Highly Conserved Conformational Epitope‐Specific Monoclonal Antibody #1‐46‐12

Abstract: The surface of the rabies virion is covered with spiky projections, each of which is thought to be composed of a homo-trimer of a single species of virus-coded glycoprotein (G) (8). The G protein is a typical type I glycoprotein, which is comprised of three parts, the ectodomain composing a major part of the protein and the remained two, the transmembrane and a short cytoplasmic C-terminal domains (4). The G protein has oligosaccharide side chains, the number of which differs among the virus strains (usually o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The sequon at Asn 158 was detected in the fixed virus strain HEP-Flury, which was established by serial passaging in chicken eggs. Irie et al (2002) found that baby hamster kidney (BHK)-21 cell-adapted HEP-Flury lost the sequon at Asn 158 . Therefore, the facilitative effect of the N-glycan at Asn 158 on virus production might be cell-type specific, although the mechanism is unknown.…”
mentioning
confidence: 99%
“…The sequon at Asn 158 was detected in the fixed virus strain HEP-Flury, which was established by serial passaging in chicken eggs. Irie et al (2002) found that baby hamster kidney (BHK)-21 cell-adapted HEP-Flury lost the sequon at Asn 158 . Therefore, the facilitative effect of the N-glycan at Asn 158 on virus production might be cell-type specific, although the mechanism is unknown.…”
mentioning
confidence: 99%
“…In present study, culture fluids of the hybridoma cells were mostly used as the mAb source. Antibody concentration of each mAb stock was estimated by semi-quantitative immunoblot assay using a mouse immunoglobulin sample of known concentration and peroxidase-conjugated anti-mouse goat antibody (Cappel) as described previously (15). Hybridoma culture fluids contained about 10 µg protein/ml of the antibody, which was sufficient for this study.…”
Section: Methodsmentioning
confidence: 99%
“…For sequencing of the G gene of mutant viruses, G cDNAs fragments were prepared from the virion RNA by an RT-PCR method using the set of primers described in our previous report (15). The first strand of G cDNA was prepared using the viral genome RNA as the template of reversetranscription by AMV reverse transcriptase, and then amplified by PCR with Taq DNA polymerase (ExTaq, TaKaRa; 23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations